STEM-PBL integrative electronic module: Is that effective in improving students' critical thinking skills? - Phandini, Intan; Miharja, Fuad Jaya; Husamah, Husamah; Fauzi, Ahmad; Nuryady, Mohammad Mirza (Jurnal Inovasi Pendidikan IPA, 2023)
The aim of this research is to develop an electronic module that integrates STEM and PBL projects to improve students' critical thinking skills. Development research conducted using the ADDIE model. The research was conducted at Muhammadiyah 2 Junior High School (JHS) of Batu. Product trials were carried out involving 25 class VII students. The data collection instrument was carried out using a questionnaire given to media experts, material experts, teachers and students to test the feasibility and practicality of the media, as well as the pretest-posttest to measure students' critical thinking skills. The results of the study show four things: 1) the E-Module learning media is in the very feasible category with a weighting percentage of eligibility, namely 77.5% by media experts and 98% by material experts. 2) E-Module learning media is included in the very practical category by science teachers with a percentage of 97%, and the practical category by students with a percentage of 79%. 3) The results of the implementation show that students are very enthusiastic in participating in learning activities using the E-Module, seen from the percentage of aspects of interest in the media which reaches 86%. 4) E-Module learning media has a significant effect so that it has the potential to improve students' critical thinking skills (Sig = 0.000). Thus, the E-Module with the STEM approach based on the PBL Model can be used in learning environmental pollution material by students.